Vertical urban design: social and public places in the sky: the Pinnacle Duxton case study Singapore - Abdul Hadi, Norhayuri Bin (2013)
One of the main underlying foundations of good cities is the quality of their social and public urban spaces. The needs for these quality spaces are uncompromising; if they lack rigor in planning and thorough implementation the affects and consequences can be dire upon the sustainability of these cities. The availability of and quality of such public places will take on increasing significance as we move towards 75% of the World's population living in urban areas by 2050 (Burdett & Rode, 2007). High-rises and tall buildings are increasingly becoming the solution in accommodating growing populations in areas opting for high-density development (Marcuse, 2000). With increasing and intensifying urbanization has come a growing awareness of the relative qualities of living, socializing and public life. This has increased the consciousness among architects, planners and developers to design social places for people to use for the many layers of social exchange within the design of high-rises and tall buildings. How do we theoretically approach the design of social and public spaces in these new evolving urban settlements? This thesis focuses upon analyzing attempts to design and realize place-making within social and public spaces of a recent high-rise residential development in Singapore. The Pinnacle @ Duxton Public Housing Project (2009) by the Housing Development Board of Singapore claims to succeed in achieving the concept of place-making within a high-rise settlement. This research utilizes post-occupancy methods from urban design theory in order to assess the perception of users and to record actual use and activity in these places. In doing so, this paper will attempt to identify the good and bad practices that make successful social and public places. The Pinnacle & Duxton Plain Public Housing has attained huge publicity for its design of public and social spaces vertically on a grand scale. Evaluation of this project by empirical testing adapted from urban design could provide a new theoretical platform to how and why it could work for future developers, councils, architects and planners alike.